Suksesi Kepemimpinan Perspektif Ibn al-Farra' - Miftahul Huda (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2005)
This study aims to examine the concept of leadership succession from the perspective of Ibn al-Farrā', a classical Islamic political scholar. The method used is qualitative with a descriptive-analytical approach, through a literature review of Ibn al-Farrā's main works, especially Al-Aḥkām al-Sulṭāniyyah, as well as other references that discuss his thoughts. The results of the study show that Ibn al-Farrā' emphasized the importance of sharia legitimacy and political stability in the process of leadership succession. He argued that a leader must have competence, fairness, and the support of the community and scholars. This concept accommodates the principle of religious authority and the political realities of his time. This study emphasizes that Ibn al-Farrā's thinking is still relevant in discussions about the contemporary Islamic leadership system, especially in relation to the mechanisms of election and legitimacy of power.